Cough · 5: The type 1 vanilloid receptor: a sensory receptor for cough. Issue 3 (25th February 2004) - Morice, A H; Geppetti, P
Abstract : Evidence is presented to support the proposal that activation of the type 1 vanilloid receptor (VR1) is an important sensory mechanism in cough.